Perancangan Museum Anatomi Tubuh Manusia di Jakarta Selatan, DKI Jakarta - Khasanah, Umi; Subagya, Karya; Endangsih, Tri (MAESTRO, 2021)
Museums are permanent, non-profit institutions, serving public needs, with an open nature, utilizing collecting, conserving, researching, communicating and exhibiting real objects to the public for the needs of the study, education and pleasure. The Human Anatomy Museum is a museum tourist building that contains the science of human anatomy and the like. This museum is a science museum. The museum will be created with the application of modern architecture by the lifestyle of modern society in South Jakarta City, DKI Jakarta. Modern architecture by prioritizing simplicity and removing some monotonous ornaments can be applied to increase the interest of museum visitors and change people's views about the old museum building, but it does not eliminate the provisions of the museum building. This is because the development of modern architecture emphasizes the simplicity of a design by adhering to form follows function (form follows function) and less is more (a little "ornament" is good).